Altered sensorimotor representations after recovery from peripheral nerve damage in neuralgic amyotrophy. (June 2020) - Lustenhouwer, Renee; Cameron, Ian G.M.; van Alfen, Nens; Oorsprong, Talitha D.; Toni, Ivan; van Engelen, Baziel G.M.; Groothuis, Jan T.; Helmich, Rick C.
Abstract: Neuralgic amyotrophy is a common peripheral nerve disorder caused by acute autoimmune inflammation of the brachial plexus. Subsequent weakness of the stabilizing shoulder muscles leads to compensatory strategies and abnormal motor control of the shoulder. Despite recovery of peripheral nerves and muscle strength over time, motor dysfunction often persists. Suboptimal motor recovery has been linked to maladaptive changes in the central motor system in several nervous system disorders. We therefore hypothesized that neuralgic amyotrophy patients with persistent motor dysfunction may have altered cerebral sensorimotor representations of the affected upper limb. To test this hypothesis, 21 neuralgic amyotrophy patients (mean age 45 ± 12 years, 5 female) with persistent lateralized symptoms in the right upper limb and 20 age- and sex-matched healthy controls, all right-handed, performed a hand laterality judgement task in a cross-sectional comparison. Previous evidence has shown that to solve this task, subjects rely on sensorimotor representations of their own upper limb, using a first-person imagery perspective without actual motor execution. This enabled us to investigate altered central sensorimotor representations while controlling for altered motor output and altered somatosensory afference. We found that neuralgic amyotrophy patients were specifically less accurate for laterality judgments of their affected right limb, as compared to healthy controls. There were no significant group differences in reaction times. Both groups used a first-person imagery perspective, as evidenced by changes in reaction times as a function of participants' own arm posture. We conclude that cerebral sensorimotor representations of the affected upper limb are altered in neuralgic amyotrophy patients. This suggests that maladaptive central neuroplasticity may occur in response to peripheral nerve damage, thereby contributing to motor dysfunction. Therapies focused on altering cerebral sensorimotor representations may help to treat peripheral nerve disorders such as neuralgic amyotrophy.